2020
DOI: 10.1097/acm.0000000000003651
|View full text |Cite
|
Sign up to set email alerts
|

Will Losing Black Physicians Be a Consequence of the COVID-19 Pandemic?

Abstract: A compelling case exists that increasing the number of Black physicians trained and practicing in the United States is one effective intervention to promote health equity and reduce the persistent health disparities that have become glaringly evident during the COVID-19 pandemic. However, the U.S. physician workforce has relatively few Black physicians. Blacks comprise approximately 13% of the U.S. population but only 5% of practicing physicians. In this Invited Commentary, the authors caution that the COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…We also explored whether mental health outcomes varied by race/ethnic group. Many have postulated that African American/Black, Latinx, and Indigenous HCWs bear the weight of the COVID-19 pandemic, as most patients are from underrepresented racial/ethnic groups and HCWs of color have disproportionately contracted COVID-19 compared with their white colleagues [37,38]. Yet, our findings suggest that African American/Black respondents had decreased risk of GAD and AUD compared with white respondents.…”
Section: Discussionmentioning
confidence: 50%
“…We also explored whether mental health outcomes varied by race/ethnic group. Many have postulated that African American/Black, Latinx, and Indigenous HCWs bear the weight of the COVID-19 pandemic, as most patients are from underrepresented racial/ethnic groups and HCWs of color have disproportionately contracted COVID-19 compared with their white colleagues [37,38]. Yet, our findings suggest that African American/Black respondents had decreased risk of GAD and AUD compared with white respondents.…”
Section: Discussionmentioning
confidence: 50%
“…However, most faculty and many staff reported negative impacts including increased responsibilities at home. While we do not know the demographics of our respondents, the disproportionate challenges being faced by women [9,10] and people of color in medicine [11] and in academia during this pandemic have been highlighted, which could have repercussions for career advancement beyond the pandemic. A third of research faculty reported increased clinical workload, which could put them at risk for negative mental health consequences [12], in addition to a decreased capacity to continue their research activities.…”
Section: Discussionmentioning
confidence: 97%
“…Black and Hispanic HCWs were more likely to be ever diagnosed of COVID-19 than their white counterparts even after adjusting for vaccination status and several sociodemographic characteristics. HCWs of colour are more likely to serve in communities of colour which typically have smaller facilities, fewer resources (including personnel), and higher patient load, all of which may increase risk of exposure and infection to HCWs in these settings 25 26 33–35. To achieve a positive equity impact, it will be important to address these constraints so that communities of colour are better empowered to respond to current and future public health threats.…”
Section: Discussionmentioning
confidence: 99%